The Influence of Cement Type on Seawater-Affected Concrete Impermeability - Arianto, Niky; Saputra, Ashar; Siswosukarto, Suprapto (Universitas Negeri Yogyakarta, 2024)
The impermeability of concrete exposed to seawater is key in maintaining long-term structural integrity. In an exposed environment, concrete must be able to protect itself from seawater penetration which can potentially cause damage, corrosion and material degradation. This study aims to investigate the effect of different types of cement on the impermeability of concrete using Ground Granulated Blast-furnace (GGBFS) as concrete filler based on gradation to obtain dense concrete, especially when exposed to seawater during the maintenance period with age variations of 7, 28, and 56 days. Three types of cement available in the general public were used, namely, type V, Portland Composite Cement (PCC), Portland Pozzolan Cement (PPC). The research method used was experimental testing with 6 variations with the dimensions of a cylinder measuring 15x15x30 cm 3 and a cube measuring 15x15x15 cm3. The results obtained in the form of compressive strength test with the highest elastic modulus is cement type V GGBFS of 48.12 MPa with elastic modulus 38153.21 MPa while the smallest is Portland Pozzolan Cement (PPC) 35.93 MPa and 26339.61 MPa for elastic modulus. In this study, concrete mixes with Ground Granulated Blast Furnace Slag (GGBFS) showed a significant increase in compressive strength over time, despite initially having lower strength than regular cement mixes. The use of GGBFS in concrete offers long-term benefits, with the potential to achieve higher compressive strengths. This study demonstrates the importance of considering treatment time and the use of GGBFS in designing more durable and robust concrete mixes.